Nerve Ultrasound Comparison Between Transthyretin Familial Amyloid Polyneuropathy and Chronic Inflammatory Demyelinating Polyneuropathy - Du, Kang; Xu, Ke; Cheng, Si; Lv, He; Zhang, Wei; Wang, Zhaoxia; Yuan, Yun; Meng, Lingchao (Frontiers in Neurology, 2021)
Backgrounds Transthyretin familial amyloid polyneuropathy (TTR-FAP) is frequently misdiagnosed as chronic inflammatory demyelinating polyneuropathy (CIDP) because of similar phenotypes in the two diseases. This study was intended to evaluate the role of nerve ultrasonography in differentiating TTR-FAP from CIDP. Methods Eighteen patients with TTR-FAP, 13 patients with CIDP, and 14 healthy controls (HC) were enrolled in this study. Consecutive ultrasonography scanning was performed in six nerves of bilateral limbs with 30 sites. CSAs and CSAs of variability data in median and ulnar nerves of different groups were calculated and compared. Results: Both TTR-FAP and CIDP showed larger CSAs at most sites of both upper and lower limbs than in HC groups. CIDP patients had larger CSAs than TTR-FAP patients at 8/15 of these sites, especially at U1-3, U5, Sci2 sites (p<0.01). However, the CSAs at above sites were not a credible index to differentiate TTR-FAP from CIDP with a low area under curve (<0.8). The CSA variability that was defined for the first time was significantly higher in CIDP than in TTR-FAP and HC groups, with high sensitivity (0.692) and specificity (0.833). The CSA variability of ulnar nerves was not significantly different between the three groups. For the TTR-FAP group, mean CSAs at each site were not correlated with different Coutinho stages, modified polyneuropathy disability, course of sensory motor peripheral neuropathy, Neuropathy Impairment Score, or Norfolk Quality of life-diabetic neuropathy score. The mean CMAP of ulnar nerves was negatively correlated with the mean CSAs of ulnar nerves. Interpretation: TTR-FAP patients had milder nerve enlargement with less variability in diameter of median nerves than those with CIDP, suggesting that nerve ultrasound can help differentiate the two neuropathies.